Role of Intestinal Ultrasound in the Evaluation of Postsurgical Recurrence in Crohn's Disease: Correlation with Endoscopic Findings - Macedo, Cláudia Patricia (2022)
Endoscopy remains the exam of choice in the evaluation of activity in Crohn's disease (CD) after surgery (ACD-AS). However, intestinal ultrasound (IUS) may represent a noninvasive alternative. The objective of this study is to determine the diagnostic accuracy of this modality compared to endoscopy. Material and Methods: This is a crosssectional study, comprising a period of 14 months, carried out in patients with established CD and ileocecal resection due to the disease. IUS (HI-VISION Avius®, Tokyo, Japan) was performed with linear probe B-mode/Doppler prior to ileocolonoscopy. IUS and ileocolonoscopy were performed on the same day by 2 specialists in Gastroenterology dedicated to ultrasound and inflammatory bowel disease, in a doubleblind mode. Collected demographic and clinical data (Harvey- Bradshaw Index [HBI]; remission ≤4), serological/fecal inflammatory parameters (leukocytes [4–10 × 109 cells/L], Creactive protein [≤0.5 mg/dL], and fecal calprotectin [<50 mg/kg]), endoscopy (Rutgeerts score: remission <i2), and ultrasound (intestinal wall thickening [≤3 mm] and digestive wall vascularization using the semiquantitative score of Limberg [absent = 0, sparse = 1, moderate = 2, and marked = 3]). Results: Thirty-nine patients (female: 64.1%, mean age: 43.5 ± 15.3 years) were included. The median post-surgery follow- up was 9 years (IQR 3–12). The Montreal classification was as follows: L1, 61.5% (n = 24); L3, 38.5% (n = 15); B1 and B2, 28.2% (n = 11); and B3, 43.6% (n = 17). Most patients were in clinical remission (87.2%; n = 34), with a mean HBI of 2.1 ± 2.2. Twenty-two patients (56.4%) had normal inflammatory markers. IUS (intestinal wall thickening >3 mm and/or Limberg score >1) was abnormal in 61.5% (n = 24) of the cases. Endoscopic remission (Rutgeerts score <i2) in 53.8% (n = 21) of the cases. Compared to endoscopy, IUS (area under the receiver operating characteristic curve [AUROC] = 0.75, p = 0.007) showed a diagnostic accuracy superior to that of inflammatory parameters (AUROC = 0.66, p = 0.083) and clinical parameters (AUROC = 0.64, p = 0.139). IUS showed a moderate concordance with endoscopy (κ = 0.5, p = 0.001), which was higher than that with inflammatory parameters (ĸ = 0.33, p = 0.041) or clinical parameters (ĸ = 0.29, p = 0.01). Conclusions: Ultrasound evaluation of the digestive wall is a noninvasive technique that shows a good diagnostic accuracy and a moderate concordance with endoscopy, being superior to clinical and serological/fecal inflammatory parameters.